Penerapan Akuntansi Forensik dalam Pendeteksian Kecurangan Melalui Psychological Capital Pada BPK RI Perwakilan Provinsi Sulawesi Barat - Edy, Sri Amalia; AM, Ahmad Mansur (Owner : Riset dan Jurnal Akuntansi, 2025)
Fraud detection is action taken to discover fraud that has occurred or is occurring. In fraud Fraud detection is action taken to discover fraud that has occurred or is occurring. In fraud detection activities, auditors begin by identifying evidence that is an indication of the possibility of fraud. Therefore, auditors need the role of forensic accounting in tracing evidence aimed at solving financial problems which combines expertise in the fields of accounting, auditing and law which aims to prove the existence of fraudulent acts. The aim to be achieved is to see the influence of the application of forensic accounting on fraud detection through the auditor's psychological factors, namely psychological capital.  This research focuses on detecting fraud committed by auditors at the Indonesian Financial Audit Agency Representative of West Sulawesi Province. The type of research used is quantitative research. The population in this study were all auditors at the BPK RI West Sulawesi Representative. The sampling technique used the sensis technique and the sample in this study was 51 people and used the quantitative method Structural Equation Modeling (SEM) with an intervening variable, namely psychological capital. The research results show that the application of forensic accounting has a positive and significant effect on fraud detection. Psychological capital has a positive and significant effect on fraud detection. Psychological capital has a positive and significant effect on fraud detection. Apart from that, this research can be used as input for auditors in their ability to prove the existence of fraud in the implementation of audit procedures.